Psychological theory of guilt in the Romanian Criminal Code - GHIGHECI CRISTINEL (Juridical Tribune, 2017)
Abstract In art. 16 paragraph (1) – (4), the new Romanian Criminal Code refers to some psychological processes, such as representation and willpower, which lead us to believe that the psychological theory of guilt has been preserved, being also mentioned in art. 19 in the old Criminal code. This theory of guilt has known many tendencies over time, entering our doctrine and legislation as the theory of representation. According to this theory when someone wants to do a certain physical act he foresees the consequences of that act, meaning that in his mind he has the representation (the image) of the natural consequences following that activity, and this representation of the result, the finality of the willful activity, is an act of conscience accompanying the act of will. These are reference points to be taken into consideration when the judiciaries analyze the criminal guilt whenever an offence has been committed under the criminal law. Keywords: guilt, theory of representation, conscience, willpower, normative theory. JEL Classification: K14